ChemInform Abstract: Intramolecular Rearrangement of α‐Amino Acid Amide Derivatives of 2‐Aminobenzothiazoles. Issue 52 (29th December 2014) - Pelletier, Jeffrey C.; Velvadapu, Venkata; McDonnell, Mark E.; Wrobel, Jay E.; Reitz, Allen B.
Abstract leading to symmetrical bisulfides